Microbial communities in carbonate precipitates from drip waters in Nerja Cave, Spain - Jurado, Valme; Del Rosal, Yolanda; Jimenez de Cisneros, Concepcion; Liñan, Cristina; Martin-Pozas, Tamara; Gonzalez-Pimentel, Jose Luis; Hermosin, Bernardo; Saiz-Jimenez, Cesareo (PeerJ, 2022)
Research on cave microorganisms has mainly focused on the microbial communities thriving on speleothems, rocks and sediments; however, drip water bacteria and calcite precipitation has received less attention. In this study, microbial communities of carbonate precipitates from drip waters in Nerja, a show cave close to the sea in southeastern Spain, were investigated. We observed a pronounced difference in the bacterial composition of the precipitates, depending on the galleries and halls. The most abundant phylum in the precipitates of the halls close to the cave entrance was Proteobacteria, due to the low depth of this sector, the direct influence of a garden on the top soil and the infiltration of waters into the cave, as well as the abundance of members of the order Hyphomicrobiales, dispersing from plant roots, and other Betaproteobacteria and Gammaproteobacteria, common soil inhabitants. The influence of marine aerosols explained the presence of Marinobacter, Idiomarina, Thalassobaculum, Altererythrobacter and other bacteria due to the short distance from the cave to the sea. Nineteen out of forty six genera identified in the cave have been reported to precipitate carbonate and likely have a role in mineral deposition.
Keywords: Nerja Cave; Carbonate precipitate; Drip water; Bacteria